Analysis of Perceived Usefulness, Perceived Ease of Use, Trust, and Sharia Financial Literature on the Adoption of Sharia Fintech by MSMEs - Imam Shoffan Hasyim; Hanif Hanif; Erike Anggraeni (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study is to analyze consumer intentions to use Sharia FinTech services. This study uses a quantitative descriptive approach to the population, namely SMEs in Bandar Lampung through the sampling technique using simple random sampling with random sampling regardless of the level of the research population. Furthermore, the sample calculation in this study uses the Slovin technique and hypothesis testing using SPSS 22. The results show that Perceived Usefulness, Trust, Islamic Financial Literacy, and all independent variables simultaneously have an influence on the adoption of Islamic FinTech by SMEs. Meanwhile, Perceived Ease of Use has no influence on the adoption of Islamic FinTech by MSMEs. The Islamic Financial Literacy variable has the greatest influence among the independent variables in this study. Keywords: Sharia FinTech, Technology Acceptance Model (TAM), and Perceived Usefulness